2017
DOI: 10.2741/4490
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis VI pathophysiology diagnosis and treatment

Abstract: Mucopolysaccharidosis VI (MPS VI), or Maroteaux-Lamy syndrome, is an autosomal recessive lysosomal storage disorder caused by deficient activity of the enzyme arylsulfatase B (ASB). Progressive accumulation of glycosaminoglycans (GAGs) in organs and tissues leads to the development of multisystem clinical manifestations. The presentation of MPS VI is genotypically and phenotypically diverse, with a large number of potential disease-causing mutations and a phenotypic spectrum ranging from very slowly to very ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
109
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 112 publications
0
109
0
2
Order By: Relevance
“…The highest number of behavior-related genes with changed expression (relative to HDFa control) was found in MPS IIIA (39 genes), and the lowest number was detected in MPS VI (8 genes). It is worth to note that Sanfilippo disease (MPS III, including the MPS IIIA subtype) is the MPS type in which the most severe behavioral disturbances are described [13][14][15], while no behavioral abnormalities occur in MPS VI [16]. Therefore, we assume that, although our transcriptomic experiments were performed with RNA isolated from fibroblasts, not neurons, information about the expression of genes involved in behavioral processes gained from such studies can be accurate.…”
Section: Resultsmentioning
confidence: 99%
“…The highest number of behavior-related genes with changed expression (relative to HDFa control) was found in MPS IIIA (39 genes), and the lowest number was detected in MPS VI (8 genes). It is worth to note that Sanfilippo disease (MPS III, including the MPS IIIA subtype) is the MPS type in which the most severe behavioral disturbances are described [13][14][15], while no behavioral abnormalities occur in MPS VI [16]. Therefore, we assume that, although our transcriptomic experiments were performed with RNA isolated from fibroblasts, not neurons, information about the expression of genes involved in behavioral processes gained from such studies can be accurate.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the patients with hernia, hepatosplenomegaly, claw hands, coarse face, valvular heart disease, and joint stiffness had higher levels of DS compared to those without these conditions, and the patients with hypermobile joints had higher KS levels than those without hypermobile joints. Previous studies have reported that HS can lead to dysfunction of the central nervous system (Coutinho et al, ; Tomatsu et al, ), that DS may principally result in soft tissue storage and skeletal involvement (Golda et al, ; Harmatz & Shediac, ), and that KS may primarily cause skeletal dysplasia and non‐bone soft tissue (Hendriksz et al, ). Our results also demonstrated these findings according to the quantitative data of urinary GAGs (DS, HS, and KS) using the LC‐MS/MS method.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical symptoms of the various types of MPS disorders can be classified into three groups according to the type of GAG accumulation. The "Visceral" group is caused by DS and includes patients with MPS I, II, VI, and VII presenting with coarse facial features, corneal clouding, adenotonsillar hypertrophy, hearing loss, upper airway obstruction, heart disease, hepatosplenomegaly, short stature, joint stiffness, and skeletal deformities (Golda, Jurecka, & Tylki-Szymanska, 2012;Harmatz & Shediac, 2017). The "Neurodegenerative" group is caused by HS and includes patients with MPS IIIA, B, C, and D, MPS I (Hurler syndrome), and the severe form of MPS II presenting with cognitive decline, hyperactivity, and behavioral disturbances (Coutinho, Lacerda, & Alves, 2012;Tomatsu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most therapeutic strategies for LSDs have tried to correct the biochemical defect by providing an exogenous supply of functional wild-type enzyme, taking advantage of the cross-correction mechanism. Enzyme replacement therapy (ERT) consists in the administration of the recombinant enzyme, usually through the intravenous (iv) route, and it has been exploited in different LSDs, like Pompe disease (Chakrapani et al 2010), type I Gaucher disease (Gonzalez et al 2013), Fabry disease (Alfadhel and Sirrs 2011) and MPS, type I (Laraway et al 2016), II (da Silva et al 2016), IVA (Tomatsu et al 2015), VI (Harmatz and Shediac 2017) and VII (Sands 2014). ERT with parenteral administration of a purified recombinant pro-enzyme has been exploited in different attenuated MPS-I variants (Barranger and O'Rourke 2001, Eng et al 2001, Kakkis et al 2001); however, the Blood Brain Barrier (BBB) severely limits the access of the enzyme (Kobayashi et al 2005), greatly reducing the impact of this strategy both on CNS and peripheral nervous system (PNS).…”
Section: Introductionmentioning
confidence: 99%